2019
DOI: 10.3126/jbpkihs.v2i1.24965
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about Neonatal Jaundice among Nepalese Mothers

Abstract: Background: Worldwide, Neonatal Jaundice is one of the most common disorders and causes of avoidable brain damage and physical and mental impairment, and probable death in newborns. It is an important contributor to the high neonatal morbidity and mortality in Nepal.Objective: To assess among mothers the knowledge about neonatal jaundice. Method:A descriptive cross-sectional study was conducted among 177 mothers in selected village with convenient sampling technique.Results: Findings revealed that around half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…In this study, 45.4% of mothers had good knowledge about neonatal jaundice. This knowledge level was better than that reported in other countries such as Nepal 23 (22%), Egypt 24 (30%) and Karbala city, Iraq 25 (34%). This may be attributed to the high proportion (83.1%) of our respondents who had graduated from university.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…In this study, 45.4% of mothers had good knowledge about neonatal jaundice. This knowledge level was better than that reported in other countries such as Nepal 23 (22%), Egypt 24 (30%) and Karbala city, Iraq 25 (34%). This may be attributed to the high proportion (83.1%) of our respondents who had graduated from university.…”
Section: Discussioncontrasting
confidence: 69%
“…Our study also found that education level was significantly associated with knowledge about neonatal jaundice, which was consistent with the results of an earlier review. 26 Due to differences in scoring algorithms or items investigating attitudes and practices, [23][24][25] it was difficult to compare attitudes and behaviours reported in our study with those from other countries. The majority (80.6%) of participants in this study had received prior health education on neonatal jaundice, which suggested that their knowledge about neonatal jaundice would be high.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation